Fotografia w filmie „Powiększenie” Michelangelo Antonioniego - Ziółkowska-Kurczuk, Natasza (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The article deals with „Blowup” movie by Michelangelo Antonioni, a masterpiece of the auteur cinema, which script is based on the short story of Julio Cortazar. This almost classic movie has autothematic character and takes up the problem of getting to know the world through image, and especially through photograph. It also refers to the problem of creation in the pop culture world. However, above all it is a metaphorical discourse about being human in the world. The author of article undertakes analysis of film in the context of photography, which is a fictional and aesthetic base and also allows to make universal considerations.